A Comparison of Reinforcement Sensitivity Theory Measures: Unique Associations With Social Interaction Anxiety and Social Observation Anxiety. (July 2018) - Kramer, Sam L.; Rodriguez, Benjamin F.
Evidence suggests that the behavior inhibition system (BIS) and fight-flight-freeze system play a role in the individual differences seen in social anxiety disorder; however, findings concerning the role of the behavior approach system (BAS) have been mixed. To date, the role of revised reinforcement sensitivity theory (RST) subsystems underlying social anxiety has been measured with scales designed for the original RST. This study examined how the BIS, BAS, and fight, flight, freeze components of the fight-flight-freeze system uniquely relate to social interaction anxiety and social observation anxiety using both a measure specifically designed for the revised RST and a commonly used original RST measure. Comparison of regression analyses with the Jackson-5 and the commonly used BIS/BAS Scales revealed important differences in the relationships between RST subsystems and social anxiety depending on how RST was assessed. Limitations and future directions for revised RST measurement are discussed.